Folk songs from Warmia and Mazury in the work of early education teachers in developing regional identity of pupils in classes I–III - Lisowska, Kinga (Kultura-Społeczeństwo-Edukacja, 2024)
Warmia and Mazury are distinct historical regions whose traditions are used in early school education as carriers of regional culture, e.g. fairy tales and folk songs. The aim of this study was to establish what role do folk songs play in shaping students’ identity in the experiences of early childhood education teachers? Qualitative research was based on individual, partly guided, problem-focused interviews. Interviews were conducted with seven early childhood education teachers from the Warmińsko-Mazurskie Voivodeship. The respondents point to a specific organization of the educational process with the use of folk songs and identify specific elements occurring in the process of implementing folk songs, which play an important role in shaping the regional identity of students in grades I–III: information about folk heroes, songs and dance games; the stories of the works’ creation; rhyming and easily catchy phrases. The development of identity in children is reinforced by the acquisition of the ability to be rooted culturally and to adapt the elements of regional songs to the present reality in which they function. The regional identity developed in this manner is stronger if the process of stimulation by the local culture – children in contact with the local tradition and history – is longer. Fairy folk songs should be permanently embedded in the education process in classes I–III.